KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN ASING DALAM MEMODERASI PENGARUH PENGHINDARAN PAJAK TERHADAP NILAI PERUSAHAAN - Arif Nugrahanto; Egra Gramatika (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2022)
This study aims to examine the effect of tax avoidance on firm value and to examine the role of managerial ownership and foreign ownership in moderating this relationship. This research uses quantitative methods and is carried out on consumer goods industry sub-sector companies listed on the IDX in 2016-2019. Using a total sample of 28 companies, it was applied with 112 total observations. This study uses Cash ETR and Current ETR to measure tax avoidance, adjusted Tobin's Q to measure firm value, managerial ownership and foreign ownership as moderator variables, and company age and size as control variables. Using panel data method, the findings are that tax avoidance has a significant positive effect on firm value. Meanwhile, the managerial ownership weakens the relationship between tax avoidance and firm value, and foreign ownership weakens the relationship between tax avoidance and firm value. Moreover, applying  Cash ETR or Current ETR as a proxy produce the different results.